THE CAUSAL RELATIONSHIP BETWEEN DEPOSIT INTEREST RATES, FOREIGN EXCHANGE RATES AND STOCK MARKET INDEX (LQ45) IN INDONESIA PRE AND POST CRISIS 2008 - Suwantono, Edwin (Jurnal Manajemen Update, 2019)
ABSTRACT The main objectives of this study is to determine the interactions between deposit interest rates, foreign exchange rates and stock market index (LQ45) in Indonesia pre and post crisis 2008. The data period before the crisis is October 2000 until November 2008. The data period after the crisis is December 2008 until December 2015. Descriptive quantitative analysis is used in this research. Descriptive analysis method is performed by using analytical table and graphic. Quantitative analysis method is performed by making a regression equation econometric model with time series method to describe the presence or absence of the influence of the independent variable towards the dependant variable. The result showed that during the pre crisis 2008, unidirectional causality existed from Deposit Interest Rates towards Foreign Exchange Rates, Stock Market Index (LQ45) towards Deposit Interest Rates, Deposit Interest Rates towards Stock Market Index(LQ45), and Stock Market Index (LQ45) towards Foreign Exchange Rates. The result post crisis 2008 showed that unidirectional causality existed from Foreign Exchange Rates towards Deposit Interest Rates, Deposit Interest Rates towards Foreign Exchange Rates, and Stock Market Index (LQ45) towards Foreign Exchange Rates. It is found that the direction of causality between the three variables tends to demonstrate a hit-and-run behavior and changes according to the lag selection. This implies that great caution should be taken when interpreting granger causality result.  Keywords: Deposit Interest Rates, Foreign Exchange Rates, Stock Market Index, LQ45, Granger Causality and Subprime MortgageBIBLIOGRAPHY (2008, September 15). Retrieved September 15, 2016, from CNBC: http://www.cnbc.com/id/26708143(2016, November 1). Retrieved from Investing: https://www.investing.com/indices/jakarta-lq45(2016, September 21). Retrieved September 12, 2016, from Consumer Financial Protection Bureau: http://www.consumerfinance.gov/askcfpb/110/what-is-a-subprime-mortgage.htmlInternational Monetary Fund (IMF)'s International Financial Statistics. (2016, October 22). Retrieved from http://data.imf.org/regular.aspx?key=60998108(2018, October 8). Retrieved October 8, 2018, from www.idx.co.id: http://www.idx.co.id/media/1482/lq45-index-methodology-by-idx.pdf(2018). Retrieved July 03, 2018, from Oxford Dictionaries: https://en.oxforddictionaries.com/definition/interest_rate(2018). Retrieved July 3, 2018, from Cambridge Dictionary: https://dictionary.cambridge.org/dictionary/english/interest-rate(2018). Retrieved July 04, 2018, from Cambridge Dictionary: https://dictionary.cambridge.org/dictionary/english/certificate-of-depositInternational Monetary Fund. (2018). Retrieved July 3, 2018, from http://data.imf.org/regular.aspx?key=61545855Ahmed, M., Rehman, R., & Raoof, A. (2010). Do interest rate, exchange rate effect stock returns? A Pakistani perspective. International Research Journal of Finance and Economics(50), 146-150.Ajayi, R., & Mougoue, M. (1996). On the dynamic relation between stock prices and exchange rates. Journal of Financial Research, 19, 193-207.Alam, M. M., & Uddin, M. G. (2009). Relationship between interest rate and stock price: Empirical evidence from developed and developing countries. International Journal of Business and Management Vol.4, No. 3, 43-51.Alam, S., Butt, M. S., & Iqbal, A. (2001). The Long-run Relationship between Real Exchange Rate and Real Interest Rate in Asian Countries: An Application of Panel Cointegration. The Pakistan Development Review, 577-602.Allaro, H. B., Kassa, B., & Hundie, B. (2011). A time series analysis of structural break time in themacroeconomic variables in Ethiopia. African Journal of Agricultural Research Vol. 6(2), 392-400.Amadeo, K. (2016, July 26). Retrieved from The Balance: https://www.thebalance.com/what-caused-2008-global-financial-crisis-3306176CEO, D. (2016, November 19). Retrieved from Tribuneindia: http://www.tribuneindia.com/news/business/fixed-deposit-best-option-for-risk-averse-investors/230726.htmlCho, D., & West, K. (2001). Interest Rates and Exchange Rates in the Korean, Philippine, and Thai Exchange Rate Crisis. NBEP, Conference on Management of Currency Crisis. Monterey, California.Chow, H. K., & Kim, Y. (2004). The Empirical Relationship Between Exchange Rates and Interest Rates in Post-Crisis Asia. School of Economics and Social Sciences, Singapore Management University.Commission, T. F. (2011). The Financial Crisis Inquiry Report. Subprime Lending, 70.Commission, T. F. (2011). The Financial Crisis Inquiry Report, Final Report Of The National Commission On The Causes Of The Financial And Economic Crisis In The United States. Washington D.C: Official Government Edition.Dash, P. (2001). The Relationship between Interest Rate and Exchange Rate in India. Indian Economic Journal.Eichenbaum, M., & Evans, C. L. (1995). Some Empirical Evidence on the Effects of Shocks to Monetary Policy on Exchange Rates. The Quarterly Journal of Economics, Vol. 110, No. 4, 975-1009.Elton, E. J., Gruber, M. J., Brown, S. J., & Goetzmann, W. N. (2003). Modern Portfolio Theory and Investment Analysis. New York: John Wiley & Sons, Inc.Fama, E. F. (1991). Efficient Capital Market : II. The Journal Of Finance. Vol 46 No.5 December 1991, 1575-1617.Fang, W. (2000). Stock market process and expected depreciation over the Asian financial crisis. Applied Economics, 2001, 33, 905-912.Furman, J., & Stiglitz, J. (1998). Economic Crisis: Evidence and Insights from East Asia. Brookings Papers on Economic Activity, 1-135.Goldfajn, I., & Gupta, P. (1999). Does Monetary Policy Stabilize the Exchange Rate Following a Currency Crisis? Working Paper of the International Monetary Fund.Granger, C. W. (1986). Developments in the Study of Cointegrated Economic Variables. Oxford Bulletin of Economics and Statistics, 213-228.Granger, C. W., & Newbold, P. (1974). Spurious Regressions In Econometrics. Journal Of Econometrics 2, 111-120.Granger, C., Huang, B. N., & Yang, C. (2000). A Bivariate Causality between Stock Prices and Exchange Rates: Evidence from Recent Asian Flu. The Quarterly Review of Economics and Finance 40, 337-354.Grant, A. (1988). Handbook of Money and Capital Market. Connecticut: Quorum Books, Greendwood Press, Inc.Gujarati, D. N. (2003). Basic Econometrics Fourth Edition. New York: McGraw-Hill.Gümüş, İ. (2003). Effects of the Interest Rate Defense on Exchange Rates During the 1994 Crisis in Turkey. Research Department Working Paper No.14 The Central Bank Of The Republic Of Turkey.Hidayat, T. (2017, February 14). Teguh Hidayat & Partners. Retrieved from http://www.thpartner.com/2016/02/what-is-lq45.htmlHyde, S. (2007). The response of Industry stock returns to market, exchange rate and interest rate risks. Managerial Finance, 693-709.Kasman, S. (2003). The relationship between exchange rate and stock prices: a causality analysis.Kayhan, S., Bayat, T., & Ugur, A. (2013). Interest Rates and Exchange Rate Relationship in BRIC-T Countries. Ege Academic Review, 227-236.Kearney, C. (1998). The causes of volatility in a small, internationally integrated stock market: Ireland, July 1975-June 1994. Journal of Financial Research, 21(1), 85-104.Keynes, J. M. (1936). The General Theory of Employment, Interest and Money. United Kingdom: Palgrave Macmillan.Koutoulas, G., & Kryzanowski, L. (1996). Macrofactor conditional volatility, time-varying risk premia and stock return behavior. Financial Review, 31, 169-195.Lean, H.-H., Halim, M., & Wong, W.-K. (2003). Bivariate Causality Between Exchange Rate and Stock Price On Major Asian Countries. Department Of Economics National University Of Singapore.Levi, M. D. (1996). International Finance The Markets and Financial Management of Multinational Business 3rd Edition. New York: McGraw-Hill, Inc.Lo, A. W. (2016). What Is An Index? The Journal Of Portfolio Management Volume 42 Number 2, 2.M, K., & S, Y. A. (2013). Macroeconomic forces and stock prices: Evidence from the Bangladesh Stock Market. Bangladesh: Dhaka.Madura, J. (2012). Financial Institutions & Markets. Florence: Cengage Learning, Inc .Mankiw, N. G. (2009). Macroeconomics Seventh Edition. New York: Worth Publishers.Markowitz, H. (1952). Portfolio Selection. The Journal of Finance, Vol. 7, No. 1., 77-91.Mbulawa, S. (2015). Stock Market Performance, Interest Rate and Exchange Rate Interactions in Zimbabwe: A Cointegration Approach. International Journal of Economics, Finance and Management VOL. 4, NO. 2, 77-88.Mishkin, F. (2011). The Economics of Money Banking and Financial Market. Fourth Canadian Edition. Toronto: Pearson Canada.Mishkin, F. S. (2010). The Economics of Money, Banking, and Financial Markets Buku 2. Jakarta: Salemba Empat.Mukherjee, T., & Naka, A. (1995). Dynamic relations between macroeconomic variables and the Japanese stock market: an application of a vector error correction model. Journal of Financial Research, 18, 223-237.Pan, Ming-Shiun, Fok, R. C.-W., & Liu, A. Y. (2000). Dynamic Linkages Between Exchange Rates and Stock Prices: Evidence from Pacific Rim Countries. Working Paper, Financial Management Association Annual Meeting.Pettinger, T. (2017, January 20). Retrieved from Economicshelp: http://www.economicshelp.org/macroeconomics/exchangerate/factors-influencing/Purna, I., Hamidi, & Prima. (2009, May 26). Perekonomian Indonesia Tahun 2008 Tengah Krisis Keuangan Global. Retrieved September 23, 2016, from Kementerian Sekretariat Negara Republik Indonesia: http://www.setneg.go.id/index.php?option=com_content&task=view&id=3698Ramasamy, B., & Young, M. (2001). The Causality between Stock Return and Exchange Rate. Research Paper Series University of Notthingham Malaysia.Sánchez, M. (2005). The Link Between Interest Rates And Exchange Rates. Do Contractionary Depreciations Make A Difference? European Central Bank Working Paper Series No.548 / November2005, 6.Saragih, F. D., & Nugroho, B. Y. (2014). Dasar - Dasar Keuangan Internasional. Jakarta: PT.Raja Grafindo Persada.Sargent, T. J., & Wallace, N. (1981). Some Unpleasant Monetarist Arithmetic. Federal Reserve Bank of Minneapolis Quarterly Review, No.5, Fall, 1-17.Saunders, A., & Cornett, M. M. (2012). Financial Markets And Institutions Fifth Edition. In A. Saunders, & M. M. Cornett, Financial Markets And Institutions Fifth Edition (p. 344). New York: McGraw-Hill/Irwin.Sharpe, W. F. (1991). The Arithmetic of Active Management. Financial Analysts Journal, 7-9.Tambunan, T. T. (2010). Modern Economy. The Indonesian Experience with Two Big Economic Crises, 156-167.Tandelilin, E. (2010). Portfolio dan Investasi. Yogyakarta: Kanisius.